Pengaruh Citra Merek Dan Kualitas Pelayanan Terhadap Keputusan Konsumen Dalam Memilih Jasa Wedding Organizer Di Purandewi Catering - Ulfi Maranisya; Bilqis Alifia Adzani (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to study how brand image and service quality impact the decisions made by customers when choosing Purandewi Catering wedding organizer services. Descriptive quantitative method with Likert measurement tool was used in this research. Primary data from this study came from 68 respondents who used Purandewi Catering services during the period January - December 2023. The results of the multiple linear regression test show that the brand image variable regression coefficient value is 0.403 or has a positive and significant effect on consumer decisions, then the service quality variable regression coefficient value of 0.298 has a positive effect on consumer decisions. The two variables also simultaneously or together have an effect on consumer decisions to use Purandewi Catering wedding organizer services with the results of the f test count 31.754 greater than the f table value of 3.13.